Tidal Phenomena and GPS-Based Monitoring System for Sea Level Measurement - Basyaruddin Ismail Harahap; Hollanda Arief Kusuma; Indri Hapsari Raharja Gultom (Journal of Applied Geospatial Information, 2025)
Measuring sea surface height in open waters is very important for understanding tidal patterns and ocean wave dynamics. Most of the instruments currently used are based on pressure or acoustic sensors and are generally placed on the coast, making them less effective for measurements in open waters. This research develops a sea surface height measurement system based on the U-Blox NEO-8M GPS, which is placed on a buoy to obtain real-time elevation data. This system consists of an Arduino Mega 2560, a GPS U-Blox NEO-8M, and a Micro SD storage module. The measurement data were analyzed using the Fourier method to identify the main components constituting the sea surface height. The test results show a Mean Tide Level (MTL) of 4.27 m, a High-Water Level (HWL) of 11.30 m, and a Low Water Level (LWL) of -6.90 m. Fourier analysis revealed eight main components that make up the sea surface height pattern, with the dominant component having a wave period of 4.29 hours and an amplitude of 6 m. The comparison between the measured data and the Fourier model resulted in an average difference of 1.0798 m, likely caused by the influence of satellite signals, multipath, and atmospheric conditions. The results of this study indicate that the GPS NEO-8M can be used as an alternative for monitoring sea surface height in open waters, although it still requires accuracy improvement through signal correction techniques and more precise geoid references.